2020
DOI: 10.1155/2020/9521073
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Pharmacology and Microbial Network Analysis with Experimental Validation to Reveal the Mechanism of Composite Sophora Colon‐Soluble Capsule against Ulcerative Colitis

Abstract: Ulcerative colitis (UC) has multifactorial pathogenesis that acts synergistically, such as immune system dysregulation and expansion of infectious gut microbiota. Therefore, a multicomponent treatment derived from Chinese herbal medicine that interacts with multiple targets synergistically is needed. Composite sophora colon-soluble capsule (CSCC) is a Chinese herbal formula that has shown therapeutic efficacy against UC in randomized clinical trials. However, its bioactive components and potential target genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Other experiments have shown that Kushen used in vivo can significantly reduce the number of invasive microbial populations in the intestines of mice, thereby lowering animal mortality caused by E. coli and Clostridium perfringens type B. Besides, Kushen was validated to inhibit NK-1R expression, leading to a reduced secretion of inflammatory cytokines such as IL-1β and IL-8 in cells and the promotion of IFN-γ synthesis ( Holleran et al, 2020 ; Ding et al, 2020 ). Consequently, this produces certain regulatory effects on abnormal immune responses in the intestinal mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other experiments have shown that Kushen used in vivo can significantly reduce the number of invasive microbial populations in the intestines of mice, thereby lowering animal mortality caused by E. coli and Clostridium perfringens type B. Besides, Kushen was validated to inhibit NK-1R expression, leading to a reduced secretion of inflammatory cytokines such as IL-1β and IL-8 in cells and the promotion of IFN-γ synthesis ( Holleran et al, 2020 ; Ding et al, 2020 ). Consequently, this produces certain regulatory effects on abnormal immune responses in the intestinal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Radix Sophorae flavescentis (Kushen) is a monarch herb in TCM formulations (Kushen-based TCM formulations) used for the treatment of UC with DHAS which has achieved good effectiveness in clinical practice and effect studies ( Tong et al, 2010 ; Tong et al, 2011 ; Gong et al, 2012 ; Fang et al, 2018 ; Chen et al, 2020 ). Kushen mainly contains the components matrine and oxymatrine , which are active ingredients against UC with significant inhibitory effects on invasive microbial populations such as Escherichia coli and Proteus mirabilis, as well as immunosuppressive effects against IL-1β and IL-17 in the intestinal epithelium ( Lin et al, 2019 ; Xu et al, 2019 ; Ding et al, 2020 ). Based on these findings, meta-analysis and network pharmacology approaches were conducted to examine the published efficacies of Kushen-based TCM formulations compared to 5-ASA in the treatment of UC, detect and identify potential pathways of Kushen against UC with DHAS, and provide evidence-based scientific support for UC treatment in clinical practice ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…IL-17 is a specific effector secreted by Th17 cells, which has a strong inflammatory effect. It promotes the production of IL-6, IL-1 β , and other inflammatory factors through recruitment, mobilization, and activation of macrophages and neutrophil granulocytes and mediates inflammatory invasion and tissue damage [ 28 ]. As a proinflammatory factor, IL-23 is involved in the formation and expansion of IL-17.…”
Section: Discussionmentioning
confidence: 99%
“…Eighteen male SD rats were randomly allocated into 3 groups: The blank group, the model group, and the treatment group with 6 rats in each group. The model group and the treatment group were induced by the administration of 3 % (w/v) dextran sulfate sodium (DSS; MP Biomedicals, USA) in distilled drinking water for 7 d, followed by distilled water for 7 d as previous described [64,65] . Rats in blank group were fed with distilled water for 14 days.…”
Section: Methodsmentioning
confidence: 99%
“…The model group and the treatment group were induced by the administration of 3 % (w/v) dextran sulfate sodium (DSS; MP Biomedicals, USA) in distilled drinking water for 7 d, followed by distilled water for 7 d as previous described. [64,65] Rats in blank group were fed with distilled water for 14 days. Dosages were calculated as previously described.…”
Section: Preparation Of Drug-containing Serummentioning
confidence: 99%